Bioprospecting secondary metabolites from Streptomyces sp. HPM-9-01/B9-A from South Kalimantan as a potential antibiotic candidate - Dwi Ariyanti; Maya Fitriana; Ali Budhi Kusuma; Matin Nuhamunada; Nurul Izzati; Aulia Reski Widyaningrum (LPPM Universitas Negeri Jakarta, 2026)
Actinobacteria of the genus Streptomyces are widely recognised as a major reservoir of antibiotics. These bacteria occur abundantly in diverse environments, including soil, freshwater, and marine ecosystems. In this study, we employed isolation, characterisation, and analytical approaches encompassing morphological, genomic, and metabolomic techniques to investigate the potential of isolate HPM-9-01/B9-A, obtained from a pine forest in Mentaos, South Kalimantan, as a candidate for antibiotic production. Morphological characterisation combined with 16S rRNA sequencing identified the strain as Streptomyces albulus. Antibacterial assays demonstrated inhibitory activity against five pathogenic bacteria, with a strong inhibition zone of 16.75 ± 2.50 mm observed for Salmonella typhimurium. LC-MS analysis, supported by secondary metabolite identification using MassLynx and ChemSpider, revealed three major compounds: C10H16N7O2, C12H18NO3, and C17H21N4O5. These metabolites are predicted to possess antibacterial and neuroactive properties. Collectively, these findings highlight the promising potential of Streptomyces sp. isolate HPM-9-01/B9-A as a source of novel antibiotic compounds.